Riociguat for the treatment of pulmonary arterial hypertension: a long-term extension study (PATENT-2) - Rubin, Lewis J.; Grünig, Ekkehard (The European respiratory journal, 2015)
Riociguat is a soluble, guanylate cyclase stimulator, approved for pulmonary arterial hypertension. In the 12-week PATENT-1 study, riociguat was well tolerated and improved several clinically relevant end-points in patients with pulmonary arterial hypertension who were treatment naïve or had been pretreated with endothelin-receptor antagonists or prostanoids. The PATENT-2 open-label extension evaluated the long-term safety and efficacy of riociguat. Eligible patients from the PATENT-1 study received riociguat individually adjusted up to a maximum dose of 2.5 mg three times daily. The primary objective was to assess the safety and tolerability of riociguat; exploratory efficacy assessments included 6-min walking distance and World Health Organization (WHO) functional class. Overall, 396 patients entered the PATENT-2 study and 324 (82%) were ongoing at this interim analysis (March 2013). The safety profile of riociguat in PATENT-2 was similar to that observed in PATENT-1, with cases of haemoptysis and pulmonary haemorrhage also being observed in PATENT-2. Improvements in the patients', 6-min walking distance and WHO functional class observed in PATENT-1 persisted for up to 1 year in PATENT-2. In the observed population at the 1-year time point, mean±sd 6-min walking distance had changed by 51±74 m and WHO functional class had improved in 33%, stabilised in 61% and worsened in 6% of the patients versus the PATENT-1 baseline. Long-term riociguat was well tolerated in patients with pulmonary arterial hypertension, and led to sustained improvements in exercise capacity and functional capacity for up to 1 year. Riociguat was well tolerated in patients with PAH, with sustained benefits in 6MWD and WHO FC for up to 1 year http://ow.ly/EskBj
Gesehen am 18.05.2017